PREVALENCE OF DIFFERENT STAGES OF PERIODONTAL DISEASES AMONG A SAMPLE OF YOUNG ADULT OBESE PATIENTS: A HOSPITAL BASED CROSS-SECTIONAL STUDY OVER 1 YEAR - Omar Marzouq M Alrasheedi, Nasser Khalief Awad Alshammari, 3. Fahad Shulaywih O Alzabni, Sami Thani Alenzi, Ibrahem Khalof Alanzi, Khaled Mohammed Alanazi (Chelonian Research Foundation, 2022)
Background: This cross-sectional study aims to investigate the prevalence of different stages of periodontal diseases based on recent classifications among young adult obese dental outpatients. Methods: A total of 314 patients receiving dental treatment participated in this study. Patients completed validated oral health questionnaires, providing demographic information such as age, gender, education level, and oral health habits. The oral health impact profile questionnaire for chronic periodontitis (OHIP-CP) was also administered. Obesity parameters were assessed using weight, height, and waist circumference to determine the stage of obesity. Diagnosis of periodontal diseases was based on clinical parameters including plaque index (PI), bleeding on probing (BoP), pocket depth (PD), clinical attachment level (CAL), and gingival recession depth (RD), supplemented by periapical radiographs. Statistical analysis included ordinal logistic regression to identify predictors of periodontal diseases and discriminant analysis to predict disease classification. Results: The study's participants, aged 19–39 years, exhibited a 100% prevalence of various periodontal disease stages. Gingivitis was the most prevalent (63.7%), followed by Periodontitis Stage III (22.6%) and Stage II (11.1%), with Stage I being the least prevalent (2.5%). A significant association was observed between increasing BMI and elevated PD, CAL, RD, and PI (P-value < 0.05). The mean OHIP-CP score for all participants was 15.99 ± 3.06. Conclusions: This study highlights a significant correlation between periodontal diseases and obesity among young adults. BMI showed a direct association with periodontal parameters, emphasizing the importance of self-assessment of oral health and obesity as predictors of periodontal disease.